(untitled) (Buana Pendidikan: Jurnal Fakultas Keguruan dan Ilmu Pendidikan Unipa Surabaya, 2022)
The purpose of this study was to determine the effect of the contextual teaching and learning model on students’ mathematical communication skills. This study uses quasi-experimental design research in the form of a time-series design. The population is all fourth-grade students of Madrasah Ibtidaiyah (MI) in Sorong City for the 2021/2022 academic year. The sampling technique used cluster random sampling, with a sample size of 30 students of MI Al-Ma’arif Sorong City. The data analysis technique in this study used the paired sample t-test. The results showed that there was a significant influence from the application of the contextual teaching and learning model on students’ mathematical communication skills.